Anatomical Analysis and Feasibility Study of Next-Generation Fenestrated or Branched Stent-Grafts for the Treatment of Arch Aneurysms. (October 2020) - Fujimura, Naoki; Ichihashi, Shigeo; Motoki, Manabu; Ohtsubo, Satoshi; Kawauchi, Yasushi; Kichikawa, Kimihiko; Shimizu, Hideyuki; Kato, Masaaki
Purpose: To analyze the anatomical characteristics of arch aneurysms and evaluate the anatomical feasibility of 4 next-generation stent-grafts with either branched or fenestrated configurations.Materials and Methods: A retrospective analysis was conducted of 213 patients (mean age 75.0±7.1 years; 179 men) with arch aneurysms treated using total arch replacement or zone 0 or 1 thoracic endovascular aortic repair (TEVAR) from 2007 to 2017 at 2 Japanese hospitals. Anatomical analyses were performed using the centerline of flow technique on a 3-dimensional workstation. The anatomical feasibility of the Zenith A-branch, TAG Thoracic Branch Endoprosthesis (TBE), Terumo Aortic Relay Plus Double Branched (DB), and fenestrated Najuta stent-grafts were evaluated based on the instructions for use (IFU).Results: The mean lengths from the sinotubular junction (STJ) to the innominate artery (IA) and from the IA to the left common carotid artery were 114.9±15.9 and 12.8±5.6 mm, respectively. The mean aortic diameters at the STJ and IA were 31.3±3.4 and 34.1±5.3 mm, respectively. In terms of feasibility, 5.2% of patients were within the Zenith A-branch IFU, 40.8% for the TAG TBE, 24.9% for the Relay Plus DB, and 13.6% for the Najuta. Significant (>50% circumference) thrombus/calcification at the sealing zone affected nearly half of the patients, but there is currently no standardized definition or evaluation method for "significant" thrombus/calcification.Conclusion: Only 5% to 41% of arch aneurysm patients are anatomically suitable for TEVAR using any one of the next-generation branched or fenestrated stent-grafts. Furthermore, a definitive method of evaluating the thrombus/calcification burden needs to be established in future IFU.